2012
DOI: 10.3122/jabfm.2012.02.110166
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Impact of Patient Safety Incidents on Family Physicians and Their Office Staff

Abstract: Objective: The objective of this study was to investigate the emotional responses and coping strategies that family physicians and their office staff reported in response to a patient safety incident.Method: Two questions contained in a patient safety incident report developed for a study of patient safety in family practice were analyzed. The questions asked reporters to indicate their emotional response to a patient safety incident and how they coped with it. A total of 264 confidential patient safety incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 33 publications
2
31
0
Order By: Relevance
“…[5][6][7][8][9][10][11][12][13][14][15] In addition, our study brought up a distinction of three different ways in which interviewees (physicians) coped during their recovery process. In a hospital without an appropriate collegial support program, the extent to which support is given depends on the willingness of a close colleague to do so.…”
Section: Recovery Processmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8][9][10][11][12][13][14][15] In addition, our study brought up a distinction of three different ways in which interviewees (physicians) coped during their recovery process. In a hospital without an appropriate collegial support program, the extent to which support is given depends on the willingness of a close colleague to do so.…”
Section: Recovery Processmentioning
confidence: 99%
“…[4] Second victims feel confused and experience emotions of anger, anxiety, guilt, grief, self-criticism, and shame. [5][6][7][8][9][10][11][12][13][14][15] These emotions have an impact on both their professional and personal lives. [14,15] Second victims therefore need time to recover from adverse events.…”
Section: Introductionmentioning
confidence: 99%
“…O'Beirne et al study in 2012 showed that 82.4% of doctors suffered from negative emotions following incidents related to patient safety. 9 Studies have also shown that even minor incidents and adverse events which resulted in no harm or complications to patients' health were associated with significant emotional response from health care providers. This was demonstrated with near miss events as well; one third of doctors reported negative emotions and increased stress at work as a result of near misses.…”
Section: Emotional Impact On Doctorsmentioning
confidence: 98%
“…7 General physicians (GPs) reported suffering from frustration (48.3%), embarrassment (31.5%), anger (12.6%), and guilt (10.1%) following an adverse clinical event. 9 The life quality at work and job satisfaction are significantly affected following medical error. Feelings of increased anxiety, loss of confidence, sleeping difficulties, reduced job satisfaction, and fear of harm to their reputation were reported by many GPs following such events.…”
Section: Emotional Impact On Doctorsmentioning
confidence: 99%
See 1 more Smart Citation